Hubungan Antara Keaktifan Berorganisasi Dengan Hasil Belajar Pengurus Osis Pada Mata Pelajaran Matematika Di SMAN 8 Padang - Ghufrani, Nadhilah; Natsir, MHD (Universitas Negeri Padang, 2024)
The low learning outcomes of students who are suspected of having a relationship in participating in student council management at SMAN 8 Padang is the background of this research. This study has the following objectives (1) to determine the description of the organizational activeness of the student council board. (2) to determine the learning outcomes of mathematics subjects of student council administrators (3) to determine the relationship between the activeness of the student council organization and the learning outcomes of mathematics subjects at SMAN 8 Padang. This research is a correlational quantitative research that aims to study the relationship between the independent variable and the dependent variable. The population of this study amounted to 33 people, and the sampling method was cluster random sampling, where 75% or 25 people were selected. The data collection technique uses data collection tools in the form of questionnaires and statement lists. The data analysis technique uses the percentage formula with the rank order formula. The results showed that: (1) The description of the organizational activities of the student council board at SMA Negeri 8 Padang is rated very high. (2) Mathematics learning outcomes of the student council board of SMA Negeri 8 are rated as moderate. (3) There is a significant relationship between the activity of the student council organization and the mathematics learning outcomes of the student council board at SMA Negeri 8 Padang. SMA Negeri 8 Padang is expected to be able to increase the motivation of student administrators to balance organizational and learning activities.